Paul Robeson's place in YouTube: A social spatial network analysis of digital heritage. (27th July 2018) - Rhodes II, Mark Alan
Abstract: This article utilizes the African American Paul Robeson and his representation on YouTube to address three critical and underexplored arenas in heritage studies. First, Paul Robeson is an individual all but lost in the public memory of the USA, despite having been one of the USA's most well-known celebrities. This article presents, for the first time, a global analysis of his representation and presence through the medium of YouTube. Second, in only a limited number of studies has YouTube been utilized to analyze memorialization and heritage; this article solidifies, channels, and expands upon those techniques. Finally, this article presents a spatial component to the otherwise nonspatial technique of analyzing YouTube social networks, presenting specific spatial data, which can be mapped and analyzed. Utilizing values of connectedness among videos of different topical clusters, as well as audience reactions to videos of a specific topic or place, allows for a deeper and broader understanding of both how Paul Robeson is memorialized and represented globally and how YouTube is an essential tool in social spatial heritage studies.